Comparison of lateral abdominal muscle thickness and cross sectional area of multifidus in adolescent soccer players with and without low back pain: A case control study - Noormohammadpour, P.; Hosseini Khezri, A.; Linek, P.; Mansournia, M. A.; Hassannejad, A.; Younesian, A.; Farahbakhsh, F.; Kordi, R. (Asian Journal of Sports Medicine, 2016)
Background: Low back pain (LBP) is a common complaint amongst adolescent athletes. While different studies have shown association between LBP and trunk muscle thickness in the general population, few articles have studied it in adolescent athletes.